Hubungan Aksesibilitas, Dukungan Tenaga Kesehatan dan Persepsi dengan Pelaksanaan Imunisasi TT Pra Nikah di Puskesmas Sukamulya Kecamatan Sukamulya Kab. Tangerang Tahun 2017 - Dina Raidanti; Wahidin Wahidin (Jurnal Ilmiah Kesehatan Delima, 2019)
The implementation of Tetanus Toxoid immunization for brides and grooms has been regulated in the Ministry of Religion Decree No.2 of 1989 N0.162 – 1/PD.0304. EI that every prospective bride must have been immunized with Tetanus Toxoid. Tetanus vaccine in women who will marry can increase immunity from tetanus infection. The purpose of this study was to determine whether there was a relationship between accessibility, support from health workers and perceptions with the implementation of pre-marital TT immunization at the Sukamulya Health Center, Sukamulya District, Tangerang Regency in 2017. The type of research used was quantitative research using a cross sectional approach. The population in this study was 120 people and the sample used was 40 people. The sampling technique was carried out by accidental sampling. Univariate and bivariate data analysis using chi square technique. From the results obtained that the distribution of the frequency of the implementation of pre-marital TT immunization that was not immunized was (75.0%), accessibility was not supported (55.0%), lack of support for health workers (52.5%) and less perception (55.0%). %). The results of the chi square test showed that there was a significant relationship between accessibility (P-value = 0.000), support from health workers (P-value = 0.001), and the implementation of pre-marital TT immunization (P-value = 0.000). From the results of this study, it was concluded that there was a relationship between accessibility, support from health workers and perceptions with the implementation of premarital TT immunization.